Peningkatan Hasil Belajar dalam Pembelajaran Tematik Terpadu Menggunakan Model Think Pair Share di SD - Putri, Nina Anggelina; Suardiman, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe the improvement of integrated thematic learning outcomes using the Cooperative type Think Pair Share (TPS) model at 4thA grade of SDN 03 Pakan Kurai, Bukittinggi City. This type of research is classroom action research and uses qualitative and quantitative approaches. The subject of this study were the 4thA grade teacher as observers, researchers as pactitioners and 29 students. The research result shows some improvements. In term of lesson plans, the score increased from 86,37% in cycle I to 95,45% in cycle II. In term of teacher’s aspect, the score enhanced from 82,82% in cycle I to 93,75% in cycle II. Meanwhile, in term of the student’s aspect, the score increased from 82,82% in cycle I to 93,75% in cycle II. Finally, the student’s learning outcomes enhanced from 75 in cycle I to 83 in cycle II.